2018
DOI: 10.1080/0886022x.2018.1496934
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of transforming growth factor-β1 and α-smooth muscle actin contributes to the protection of lotensin against chronic renal failure in rats

Abstract: Background: Lotensin has been shown to have a protective function in the early stage of chronic renal failure. However, its role in the intermediate and late stages of chronic renal failure remains largely unknown. The present study aimed to investigate the role and underlying mechanism of lotensin in advanced chronic kidney disease.Methods: Female Wistar rats were randomly divided into three groups (n = 10): sham group, 5/6 nephrectomy (5/6 Nx) group, and lotensin group (oral administration of lotensin for 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
4
1
1
Order By: Relevance
“…Modern medical research has demonstrated that the primary pathological changes of CRF include general atrophy and fibrosis of glomerulus, hypertrophy, necrosis, and occlusion of renal tubular, leading to glomerular sclerosis and interstitial fibrosis [ 28 ] . Mesangial cells act as the supporting structure of glomerular capillaries, their contractions are essential to maintain normal renal physiological functions and the development of renal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Modern medical research has demonstrated that the primary pathological changes of CRF include general atrophy and fibrosis of glomerulus, hypertrophy, necrosis, and occlusion of renal tubular, leading to glomerular sclerosis and interstitial fibrosis [ 28 ] . Mesangial cells act as the supporting structure of glomerular capillaries, their contractions are essential to maintain normal renal physiological functions and the development of renal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…With the standard protocol being followed prior to HE staining described above, the sections were subjected to antigen retrieval and blocking as previously described [15]. For the immunohistochemical analysis, the sections were initially incubated with mouse anti- α -SMA antibody (Abcam, Cambridge, MA, USA) or mouse anti-TGF- β 1 antibody (Thermo Fisher Scientific, Inc., Waltham, MA, USA) at 4°C overnight and were then incubated with HRP-conjugated goat antimouse secondary antibody (Abcam, Cambridge, MA, USA) at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, α-SMA, as a common marker for smooth muscle cells and myofibroblasts, is highly expressed in kidneys, and the overproduction of α-SMA partially results from tubular epithelial-myofibroblast transdifferentiation, which plays an important role in renal interstitial fibrosis [57,58]. Consequently, the upregulation of TGF-β1 and α-SMA correlates with the risk of chronic renal failure [59].…”
Section: Discussionmentioning
confidence: 99%